Importance of HbA1c and fructosamine as a marker of glycemic control and evaluation of some biochemical parameters during pregnancy - Ayyildiz, Hakan; Kalayci, Mehmet; Yilmaz, Musa (Walter de Gruyter Gmbh, 2015)
[Abstract Not Available]
Gebelik döneminde HbA1c ve fruktozaminin glisemik kontrol belirteci olarak önemi ve bazı biyokimyasal parametrelerin değerlendirmesi